2004
DOI: 10.1136/adc.2003.042499
|View full text |Cite
|
Sign up to set email alerts
|

Could nursery rhymes cause violent behaviour? A comparison with television viewing

Abstract: Aims: To assess the rates of violence in nursery rhymes compared to pre-watershed television viewing. Methods: Data regarding television viewing habits, and the amount of violence on British television, were obtained from Ofcom. A compilation of nursery rhymes was examined for episodes of violence by three of the researchers. Each nursery rhyme was analysed by number and type of episode. They were then recited to the fourth researcher whose reactions were scrutinised. Results: There were 1045 violent scenes on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Although Alice did not seem to become fearful and anxious upon reading this poem, the story contains pieces of information that refer to the potential dangerousness of the Jabberwock, Jubjub bird, and Bandersnatch (e.g., beware, bite, claws). Threat information has, for centuries, formed an intrinsic part of culture, folklore and society (Ragan 2006 ): around 41% of a sample of nursery rhymes was violent in some way (Davies et al 2004 ). Whether it was gathered around fires, or huddled in houses, or even sat at the bedside, people have recounted folktales that have been both allegories of real danger or ways to turn fear into hope or action (Ragan 2006 ; Zipes 1979 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although Alice did not seem to become fearful and anxious upon reading this poem, the story contains pieces of information that refer to the potential dangerousness of the Jabberwock, Jubjub bird, and Bandersnatch (e.g., beware, bite, claws). Threat information has, for centuries, formed an intrinsic part of culture, folklore and society (Ragan 2006 ): around 41% of a sample of nursery rhymes was violent in some way (Davies et al 2004 ). Whether it was gathered around fires, or huddled in houses, or even sat at the bedside, people have recounted folktales that have been both allegories of real danger or ways to turn fear into hope or action (Ragan 2006 ; Zipes 1979 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, reading children' s literature revealed 52 acts of violence. In spite of the fact that only 44% of children' s literature consisted of some elements of violence, the level of aggression and violence in the literature was twice that contained in television broadcasts (Davies et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A paper published in the German journal Praxis der Kinderpsychologie und Kinderpsychiatrie compared the psychological effects of superhero comics and nursery rhymes. 1 Although nursery rhymes have been shown to have increased levels of violence compared with pre-watershed television viewing, 2 Hammon concluded that ''superhero comics are dangerous for severely disturbed children, but fairy tales are certainly beneficial''. The American National Association for the Education of Young Children (http://www.naeyc.org) produces a help sheet for parents called ''When children imitate superheroes''.…”
Section: Discussionmentioning
confidence: 99%